Increased acetyl group availability enhances contractile function of canine skeletal muscle during ischemia. - Timmons, J A (1996)
Skeletal muscle contractile function is impaired during acute ischemia such as that experienced by peripheral vascular disease patients. We therefore, examined the effects of dichloroacetate, which can alter resting metabolism, on canine gracilis muscle contractile function during constant flow ischemia. Pretreatment with dichloroacetate increased resting pyruvate dehydrogenase complex activity and resting acetylcarnitine concentration by approximately 4- and approximately 10-fold, respectively. After 20-min contraction the control group had demonstrated an approximately 40% reduction in isomeric tension whereas the dichloroacetate group had fatigued by approximately 25% (P < 0.05). Dichloroacetate resulted in less lactate accumulation (10.3 +/- 3.0 vs 58.9 +/- 10.5 mmol.kg-1 dry muscle [dm], P < 0.05) and phosphocreatine hydrolysis (15.6 +/- 6.3 vs 33.8 +/- 9.0 mmol.kg-1 dm, P < 0.05) during contraction. Acetylcarnitine concentration fell during contraction by 5.4 +/- 1.8 mmol.kg-1 dm in the dichloroacetate group but increased by 10.0 +/- 1.9 mmol.kg-1 dm in the control group. In conclusion, dichloroacetate enhanced contractile function during ischemia, independently of blood flow, such that it appears oxidative ATP regeneration is limited by pyruvate dehydrogenase complex activity and acetyl group availability.